Peripherally derived myeloid cells induce disease-dependent phenotypic changes in microglia - Thougaard, Estrid; Carney, Brianna; Wlodarczyk, Agnieszka; Brambilla, Roberta; Lambertsen, Kate Lykke (Frontiers in Cellular Neuroscience, 2023)
In central nervous system (CNS) injury and disease, peripherally derived myeloid cells infiltrate the CNS parenchyma and interact with resident cells, propagating the neuroinflammatory response. Because peripheral myeloid populations differ profoundly depending on the type and phase of injury, their crosstalk with CNS resident cells, particularly microglia, will lead to different functional outcomes. Thus, understanding how peripheral myeloid cells affect the phenotype and function of microglia in different disease conditions and phases may lead to a better understanding of disease-specific targetable pathways for neuroprotection and neurorepair. To this end, we set out to develop an in vitro system to investigate the communication between peripheral myeloid cells and microglia, with the goal of uncovering potential differences due to disease type and timing. We isolated peripheral myeloid cells from mice undergoing experimental autoimmune encephalomyelitis (EAE), a model of multiple sclerosis, or acute cerebral ischemia by permanent middle cerebral artery occlusion (pMCAO) at different times after disease and probed their ability to change the phenotype of primary microglia isolated from the brain of adult mice. We identified changes not only dependent on the disease model, but also on the timepoint after disease onset from which the myeloid cells were isolated. Peripheral myeloid cells from acute EAE induced morphological changes in microglia, followed by increases in expression of genes involved in inflammatory signaling. Conversely, it was the peripheral myeloid cells from the chronic phase of pMCAO that induced gene expression changes in genes involved in inflammatory signaling and phagocytosis, which was not followed by a change in morphology. This underscores the importance of understanding the role of infiltrating myeloid cells in different disease contexts and phases. Furthermore, we showed that our assay is a valuable tool for investigating myeloid cell interactions in a range of CNS neuroinflammatory conditions.